HUBUNGAN KADAR TARTRAZIN DAN SENG (ZN) DALAM DARAH PADA ANAK PENDERITA DEFISIT PERHATIAN DAN GANGGUAN HIPERAKTIVITAS (ADHD) - Batubara, Melvariani Syari; Siregar, Yahwardiah; Rusmarilin, Herla; Soviani, Sri; Febriani, Husnarika (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2017)
This research aims to study Tartrazine and Zinc (Zn) status in blood sample of Attention Deficit Hyperactivity Disorder (ADHD) children. Deductive research using the descriptive method through 3 stage, namely : 1. Taken of blood sample, 2. Analysis of Tartrazine status in blood sample was performed by using High Performance Liquid Chromatograpy (HPLC) method, and 3. Analysis of Zinc (Zn) status in blood sample were measurements by using Atomic Adsorbance Spectrophotometry (AAS) method. Data were analyzed using descriptive analysis techniques and Chi Square tests (X2) by Computer programs (SPSS 15). The result of the assessment of Tartrazine status in blood sample of ADHD children that had been was considered statistically highly significant a increase of the assessment of Tartrazine status in blood sample of ADHD children by 130 mg/ml compared with laboratory reference (control) by 28 mg/ml, HA>C** (p<0,001). The result of the assessment of Zinc (Zn) status in blood sample of ADHD children that had been was showed statistically highly significant a reduce of the assessment of Zinc (Zn) status in blood sample of ADHD children by 0,37 Âµg/ml compared with laboratory reference (control) by 0,64-1,18 Âµg/ml, HA<C** (p<0,001). This was considered a reduction and increase in Tartrazine and Zinc (Zn) concentrations induces of the Hyperactivity children by 95%.